3D printing in the manufacture of orthoses to correct children’s flatfoot - Tavares, Gustavo dos Santos; Nogueira Junior, Pedro Andre (Journal of the Foot & Ankle, 2025)
Objective: To analyze, through an integrative literature review, the available evidence on the technical aspects, clinical impacts, economic viability, and challenges of adopting three-dimensional (3D) technology in the pediatric context. Methods: The search was conducted on PubMed, Scopus, SciELO, and Web of Science databases, using specific keywords and previously defined inclusion and exclusion criteria. The data were synthesized descriptively and compared with the existing literature. Results: 3D printing allows the production of customized orthoses with high anatomical precision and shorter manufacturing time, presenting clinical benefits such as improved function, reduced pain, and increased adherence to treatment. The economic analysis suggests potential cost reduction in the medium term, although strategies are needed to expand access to technology. Conclusion: 3D printing in the manufacture of orthoses to correct children’s flatfoot is a promising technological alternative, capable of favoring higher anatomical precision, comfort, and potential cost reduction compared to traditional methods. Level of Evidence I; Systematic Review.